Pumpkin Seed Oil Extracted From Cucurbita maxima Improves Urinary Disorder in Human Overactive Bladder - Nishimura, Mie (Medknow Publications & Media Pvt Ltd, 2014)
The pumpkin seed oil obtained from Cucurbita pepo has been shown to be useful for the treatment of nocturia in patients with urinal disorders in several western countries. In this study, we evaluated the effect of the pumpkin seed oil from Cucurbita maxima on urinary dysfunction in human overactive bladder (OAB). Forty-five subjects were enrolled in this study. An extract of pumpkin seed oil from C. maxima (10 g of oil/day) was orally administrated for 12 weeks. After 6 and 12 weeks, urinary function was evaluated using Overactive Bladder Symptom Score (OABSS). Pumpkin seed oil from C. maxima significantly reduced the degree of OABSS in the subjects. The results from our study suggest that pumpkin seed oil extracts from C. maxima as well as from C. pepo are effective for urinary disorders such as OAB in humans.